Single-Cell Transcriptomics of Cultured Amniotic Fluid Cells Reveals Complex Gene Expression Alterations in Human Fetuses With Trisomy 18 - Wang, Jing; Chen, Zixi; He, Fei; Lee, Trevor; Cai, Wenjie; Chen, Wanhua; Miao, Nan; Zeng, Zhiwei; Hussain, Ghulam; Yang, Qingwei; Guo, Qiwei; Sun, Tao (Frontiers in Cell and Developmental Biology, 2022)
Trisomy 18, commonly known as Edwards syndrome, is the second most common autosomal trisomy among live born neonates. Multiple tissues including cardiac, abdominal, and nervous systems are affected by an extra chromosome 18. To delineate the complexity of anomalies of trisomy 18, we analyzed cultured amniotic fluid cells from two euploid and three trisomy 18 samples using single-cell transcriptomics. We identified six cell groups, which function in development of major tissues such as kidney, vasculature and smooth muscle, and display significant alterations in gene expression as detected by single-cell RNA-sequencing. Moreover, we demonstrated significant gene expression changes in previously proposed trisomy 18 critical regions, and identified three new regions such as 18p11.32, 18q11 and 18q21.32, which are likely associated with trisomy 18 phenotypes. Our results indicate complexity of trisomy 18 at the gene expression level and reveal genetic reasoning of diverse phenotypes in trisomy 18 patients.